Where people, animals and the environment are intimately connected: A look at One Health in Africa - International Livestock Research Institute (International Livestock Research Institute, 2021)
This short film highlights One Health practice for sustainable and resilient livestock production in sub-Saharan Africa. One Health is a multidisciplinary and multisectoral approach for addressing public health issues.